The Influence of Green Innovation, Customer Co-Creation, and Brand Activism on the Competitive Advantage of Organic Food MSMEs in Jakarta - Wijayanto, Gatot; Mu'min, Halek; Pahrijal, Rival (Westscience Press, 2025)
This study examines the influence of green innovation, customer collaboration, and brand activism on the competitive advantage of organic food micro, small, and medium enterprises (MSMEs) in Jakarta. With increasing consumer demand for environmentally friendly and ethically produced goods, MSMEs face the challenge of aligning business practices with sustainability and social values. A quantitative research design was applied using survey data from 150 MSME owners and managers. Respondents completed a structured questionnaire measured on a 1–5 Likert scale, and data were analyzed using SPSS version 25. The results show that green innovation, customer collaboration, and brand activism each have a positive and significant effect on competitive advantage. Green innovation emerged as the strongest predictor, emphasizing the importance of eco-friendly practices in differentiating products and improving operational efficiency. Customer collaboration also contributed positively, highlighting the role of co-creation and consumer trust in sustaining market relevance. Similarly, brand activism significantly enhanced competitive advantage, reflecting that MSMEs advocating for sustainability and social causes build stronger loyalty and brand differentiation. The findings contribute to the literature on sustainable entrepreneurship and provide practical implications for MSMEs in developing competitive strategies that integrate innovation, customer engagement, and socially responsible branding.